Trimetallic Spinel NiCo2−xFexO4 Nanoboxes for Highly Efficient Electrocatalytic Oxygen Evolution - Huang, Yi; Zhang, Song Lin; Lu, Xue Feng; Wu, Zhi‐Peng; Luan, Deyan; Lou, Xiong Wen (David) (Angewandte Chemie International Edition, 2021)
The development of efficient and low‐cost electrocatalysts toward the oxygen evolution reaction (OER) is critical for improving the efficiency of several electrochemical energy conversion and storage devices. Here, we report an elaborate design and synthesis of porous Co‐based trimetallic spinel oxide nanoboxes (NiCo2−xFexO4 NBs) by a novel metal‐organic framework engaged strategy, which involves chemical etching, cation exchange, and subsequent thermal oxidation processes. Owing to the structural and compositional advantages, the optimized trimetallic NiCo2−xFexO4 NBs (x is about 0.117) deliver superior electrocatalytic performance for OER with an overpotential of 274 mV at 10 mA cm−2, a small Tafel slope of 42 mV dec−1, and good stability in alkaline electrolyte, which is much better than that of Co‐based bi/monometallic spinel oxides and even commercial RuO2. Co‐based trimetallic spinel oxide nanoboxes are synthesized through an elaborate strategy involving chemical etching, cation exchange and thermal oxidation processes. The unique structural and compositional advantages endow the trimetallic NiCo2−xFexO4 nanoboxes with superior electrocatalytic activity and stability toward oxygen evolution reaction.